Evaluation of root and root canal morphology in maxillary premolar teeth: A cone-beam computed tomography study using two classification systems in a Japanese population - Satoshi Watanabe; Sonoko Yabumoto; Takashi Okiji (Journal of Dental Sciences, 2025)
Background/purpose: Inadequate knowledge increases the risk of overlooking root canals and causing procedural errors that can lead to root canal treatment failure. This study aimed to analyze the root and root canal morphology in maxillary premolar teeth using two classification systems assessed by cone-beam computed tomography (CBCT) in a large Japanese population. Materials and methods: This study evaluated 1443 maxillary teeth including 726 first and 717 s premolars, from 642 Japanese individuals aged 16–84 years. CBCT images were analyzed according to the Vertucci and Ahmed classification systems, focusing on the root and root canal morphology. Variations were analyzed based on gender and age using the chi-square test (P < 0.05). Results: Maxillary first premolars were predominantly single-rooted (64.9%) and had two root canals (86.2%). Females exhibited a higher prevalence of single-rooted (71.0%) compared to males (49.8%) (P < 0.05). Additionally, single root canals occurred significantly more frequently in females (14.0%) than in males (7.5%) (P < 0.05). Maxillary second premolars mostly had a single root (97.8%) with a single root canal (72.1%). The frequency of second premolars with two root canals significantly increased with age (P < 0.001). The three-rooted configuration occurred in 1.2% and 0.3% of the first and second premolars, respectively. Conclusion: Maxillary premolars in a Japanese population showed significant anatomical variations, highlighting the importance of understanding anatomical characteristics specific to age and gender. Ahmed's system provides a more comprehensive description of the morphological variations.